An innovative climate adaptation planning process: iDEAL project. (1st September 2022) - Lucertini, Giulia; Di Giustino, Gianmarco; dall'Omo, Carlo Federico; Musco, Francesco
Abstract: Climate change triggers increasing stresses on urban settlements and coastal areas. The intensification of climate-connected impacts requires municipalities and communities to undertake adaptation measures and plans. These interventions should be capable of reducing negative climatic effects on human habitat and regional bioregions. On the one hand, the international scientific community recognized the supported adaptation planning approach as the more suitable to cope with local needs and criticalities. On the other hand, there is a lack of practical guidelines and examples that can be used to implement the theory. From a perspective of growth of global awareness and sensitivity to the climatic emergency, it is necessary to develop a practical methodology able to link together impacts perception and public decision process at the local scale. The paper aims to fill the gap between the theoretical approach and the practice, through a replicable experience of integration among climate change adaptation concepts and decision-making processes. The proposed methodology is described in a 4-step process to support decision-makers in selecting tailored adaptation policies and measures. The article is based on the experience developed within the Interreg It-Hr project "iDEAL – Decision support for Adaptation pLan" project. The research combines a quantitative and qualitative methodology in local participation processes. The approach is tested on five Mediterranean coastal cities and allowed to support the development of tailored adaptation measures. Furthermore, the interaction with local actors during the process led to an acceptance of the implemented measures, designing each measure to stakeholders' ambitions and expectations. Highlights: Local participation in climate change adaptation processes. Climate impacts management and risk perception. A decision support system to enhance local decision making. Developing transboundary Adriatic coasts adaptation planning.